2014
DOI: 10.1380/ejssnt.2014.423
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Situ </i>Microfabrication and Measurements of Bi<sub>2</sub>Se<sub>3 </sub>Ultrathin Films in a Multichamber System with a Focused Ion Beam, Molecular Beam Epitaxy, and Four-Tip Scanning Tunneling Microscope

Abstract: Ultrathin films of Bi2Se3 grown on Si(111) substrate were etched into submicron-width wires by using a focused ion beam (FIB), and their electrical resistance was measured using the four-probe method with a four-tip scanning tunneling microscope. All of the procedures were performed in situ in ultrahigh vacuum without exposing the sample to air. One-dimensional conduction of the films was confirmed from the dependence of the resistance on the length of wire under measurement, meaning that successful lossless c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Directly growing nanotstructures bottom-up into the necessary geometries and defect densities would be ideal, but controlled growth and scaling of such devices is complicated. An alternative is to use top-down methods, such as ion milling, to modify the Bi 2 Se 3 [16][17][18][19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Directly growing nanotstructures bottom-up into the necessary geometries and defect densities would be ideal, but controlled growth and scaling of such devices is complicated. An alternative is to use top-down methods, such as ion milling, to modify the Bi 2 Se 3 [16][17][18][19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…1. FIB milling utilizes Ga + ions to sputter away a target material and can be used to both sculpt the material 16,17,21,22 and introduce defects 18,21 . Recent transport studies have shown that FIB-created nanowires of Bi 2 Se 3 exhibit increased photoconductivity at room temperature 22 and retain signatures of their topological surface states at low temperature 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…This opens up an interesting expectation for ultralow energy-consumption devices by using spin current. Figure 14(b) is an example of such a device, fabricated by focussed ion beam in UHV combined with four-tip STM system [56]. The electric current I is made flow through leads at the center and the volt age V is measured between leads apart from the current leads by distance L; the spin current is expected to flow along the horizontal strip of a topologocal insultor.…”
Section: Spin Transport At Surfacesmentioning
confidence: 99%
“…Iwata 等人 [82] 和Bolopion等人 [83] 分别开发了具有实时触觉 反馈的纳米镊子系统, 他们采用不同的偏转检测方 法, Iwata等人利用自检测探针, 而Bolopion等人采用 的是激光反射法. [59] , ZnO [60] QP-STM Bi 2 Se 3 [61] , CoSi 2 [43,62] 二维 DP-STM Au表面 [63] , 3-octylthiophene薄膜 [64,65] , 石墨烯 [66,67] DP-AFM α-sexithiophene [44] , 并五苯薄膜 [68] QP-STM 石墨烯 [69,70] , Si(111)4×1-In [71] , Bi 2 Te 2 Se表面 [72,73] , Pentacene薄膜 [74,75] , Au表面 [76] , Te/Si(111)-(1×1)界面 [77] 评 述 图 6 DP-AFM并行成像与操作 [33] . (a) 并行成像与操作纳米颗粒的示意图.…”
Section: 在测量时两端探针加一个偏压 中间第3个探针移动unclassified